MiR-217 regulates autophagy through OPG/RANKL/RANK in giant cell tumors - Chenyang Meng; Boyong Jiang; Wanlin Liu; Lianjuan Wang; Zhenqun Zhao; Rui Bai; Yan Zhao (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Background Increasing evidence suggests that microRNAs (miRNAs) play a crucial role in cancer development and progression. Our previous study showed remarkably lower levels of miR-217 in GCT cells and tissues, and miR-217 re-expression inhibited the occurrence and development of GCT in vitro; however, the associated mechanisms remain unknown. Thus, this study aimed to explore the mechanisms underlying the proliferation inhibitory effect of miR-217 in GCT cells. Methods The proliferative potential of the GCT cells was measured with an MTT assay and BrdU straining. Changes in GCT cell migration and invasion was assessed by a transwell assay. Finally, Western blot and RT-PCR assays were employed to evaluate OPG/RANKL/RANK signaling pathway-related protein expression. Results The excessive upregulation of miR-217 markedly suppressed GCT cell proliferation and tumorigenesis both in vitro and in vivo. miR-217 overexpression could inhibit the OPG/RANKL/RANK signaling pathway in vitro and in vivo. Furthermore, ALP activity was significantly decreased in GCT cells following miR-217 treatment. Importantly, miR-217 could inhibit autophagy-related protein expression and autophagosome/autolysosome formation in GCT cells and tissues. Conclusion These results suggest that miR-217 upregulation could inhibit the occurrence and development of GCT by blocking autophagy. These findings offer an effective therapeutic target to improve the survival rates of patients with CGT in the future.